Evaluating the immunomodulatory responses of LdODC‐derived MHC Class‐II restricted peptides against VL. (6th February 2020) - Pandey, RajKishor; Dikhit, Manas Ranjan; Kumar, Avinash; Dehury, Budheswar; Pandey, Krishna; Topno, Roshan Kamal; Das, Pradeep; Bimal, Sanjiva
Abstract: In a bid to develop a novel immunoprophylactic measure against visceral leishmaniasis (VL), MHC class‐II–restricted epitopes of Ld ODC were identified by reverse vaccinology approach. Five consensus HLA‐DRB1*0101‐restricted epitopes were screened. The analysis revealed that the set of epitopes was presented by at least 54 diverse MHC class‐II alleles. Based on in silico screening, followed by molecular dynamics simulation, population coverage analysis, and HLA cross‐presentation ability, five best epitopes were evaluated. PBMCs isolated from treated VL subjects, when stimulated with synthetic peptide alone or as a cocktail of peptides, triggered a secretory IFN‐γ, but not the IL‐10 level. Support in this notion came from intracellular cytokine level with a considerable up‐regulated IFN‐γ produced by CD4 + T cells. Also, the enhanced IFN‐γ seemed to be augmented with the activation of macrophages with prominent IL‐12 production. Therefore, it can be concluded that the screened MHC class‐II–restricted epitope hotspots derived from Leishmania ODC can trigger CD4 + T cells, which can skew macrophage functions towards protection. However, a detailed analysis can explore its potentiality as a vaccine candidate.